An additional pulsating mode (7.35 mHz) and pulsations timing variations of PG 1613+426 - Otani Tomomi; Oswalt Terry D.; Majewski Patrice; Jordan Riley; Amaral Marc; Moss Adam (Open Astronomy, 2017)
We present the detection of an additional pulsation mode (7.35 mHz) of a subdwarf B star, PG 1613+426, and periodic Observed minus Calculated (O-C) variations for two existing pulsations. PG 1613+426 is near the hot end of the sdB instability strip. One pulsation mode (6.94 mHz) was detected so far by Bonanno et al. (2002) and another pulsation mode candidate (7.05 mHz) was proposed with a confidence level above 90% by Kuassivi and Ferlet (2005). To constrain sdB star evolutional scenarios, this star was monitored in 2010, 2011, 2015, and 2017 as a part of a project for finding companions to sdB stars using the pulsation timing method. The photometric analysis of those data shows an additional 7.35 mHz pulsation mode as well as the previously detected 6.93 mHz mode. However the 7.05 mHz mode was not detected. Nightly amplitude changes of 7.35 mHz mode were observed in the 2011 data, however the 2017 data did not show nightly amplitude shifts. O-C variations were detected in both 6.93 mHz and 7.35 mHz pulsations, indicating that PG 1613+426 may have a low mass companion star. However, more observations are needed to confirm it.